2008
DOI: 10.1111/j.1471-6402.2008.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Sexual Assault Risk Reduction and Self-Defense Program: A Prospective Analysis of a Revised Protocol

Abstract: The current study extends the development and evaluation of an existing and previously evaluated sexual assault risk reduction program with a self-defense component for college women (N = 300). The program protocol was revised to address psychological barriers to responding assertively to risky dating situations, and a placebo-control group was utilized rather than a wait-list control group. Relative to the placebo-control group, the program was effective in increasing levels of self-protective behaviors, self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
166
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(172 citation statements)
references
References 55 publications
4
166
2
Order By: Relevance
“…Note, however, that other studies with self-defense components did not report such findings [41,[48][49][50]. Also note that this study (Hollander) is not without flaws.…”
Section: Acta Psychopathologica Issn 2469-6676contrasting
confidence: 46%
See 1 more Smart Citation
“…Note, however, that other studies with self-defense components did not report such findings [41,[48][49][50]. Also note that this study (Hollander) is not without flaws.…”
Section: Acta Psychopathologica Issn 2469-6676contrasting
confidence: 46%
“…Hanson and Gidycz's study [39] found that the treatment only demonstrated success for women with no histories of victimization; a subsequent study, Gidycz et al [40], found that only moderately victimized women benefited from the treatment (where "moderate victimization" includes, for example, any sexual victimization other than rape). In a later study, Gidycz et al [41] found the converse, with only severely victimized women benefiting from treatment.…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 86%
“…These results contrast with previous reports of the limited effectiveness of other interventions for women. [17][18][19][20][21] An early version of one program reduced the risk of completed rape after 9 weeks of follow-up only among women with no history of victimization. 17 In three of four subsequent studies assessing modified programs, there was no significant reduction in the risk of completed rape; in the fourth, the risk of completed rape was reduced but not beyond 2 months after the intervention.…”
Section: Discussionmentioning
confidence: 98%
“…16 Workshops designed to help women resist sexual assault or reduce their risk have had inconsistent effects. Two studies showed shortterm benefit, which in one study was limited to women who had had no previous victimization 17,18 ; other studies showed no clear benefits at 2, 4, or 6 months, even with "booster" sessions (i.e., sessions that review or expand on content to maintain or improve effects). [19][20][21] All but one study was conducted at a single site, two used grouplevel randomization, 17,19 and the one with the longest follow-up had a high rate of attrition.…”
mentioning
confidence: 96%
“…A focus on factors that may increase perceptions of sexual power (e.g., sexual assertiveness, risk appraisal, and effective resistance strategies) may strengthen young women's sense of sexual self-efficacy. Indeed, research shows that interventions focusing on sexual assertiveness and self-efficacy can reduce women's risk for sexual victimization (Orchowski, Gidycz, & Raffle, 2008). Nonetheless, it is important to emphasize that such messages are not meant to suggest victims have done anything wrong, nor that they should have done anything that they did not.…”
Section: Discussionmentioning
confidence: 99%